2021
DOI: 10.2174/1389557519666190611124539
|View full text |Cite
|
Sign up to set email alerts
|

Natural Terpenoids as Neuroinflammatory Inhibitors in LPS-stimulated BV-2 Microglia

Abstract: Background: Neuroinflammation is a typical feature of many neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease. Microglia, the resident immune cells of the brain, readily become activated in response to infection or injury. Uncontrolled and overactivated microglia can release pro-inflammatory and cytotoxic factors and are the major culprit in neuroinflammation. Hence, research into novel neuroinflammatory inhibitors is of paramount importance for the treatment of neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Experimental and clinical studies have suggested the beneficial effects of herbal medicine in neurodegenerative conditions. Previous studies have indicated that plant-derived terpenoids positively affect neurodegeneration . BAs are triterpenoid and hydrophobic compounds extracted from the resin of Boswellia plant species and they possess anti-inflammatory, antioxidant, and antiedema properties. It has been shown that BA can ameliorate memory deficit in animal AD models .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies have suggested the beneficial effects of herbal medicine in neurodegenerative conditions. Previous studies have indicated that plant-derived terpenoids positively affect neurodegeneration . BAs are triterpenoid and hydrophobic compounds extracted from the resin of Boswellia plant species and they possess anti-inflammatory, antioxidant, and antiedema properties. It has been shown that BA can ameliorate memory deficit in animal AD models .…”
Section: Introductionmentioning
confidence: 99%
“…Though PD is a subject of great concern, its exact etiology remains unclear. Researchers have postulated that oxidative stress, mitochondrial dysfunction, neuroinflammation, and apoptosis lead to DA neuronal damage. In PD, progressive loss of DA neurons occurs in the substantia nigra pars compacta. Human monoamine oxidase (hMAO) is a flavoenzyme that catalyzes the oxidative deamination of various bioamines; its inhibitors were the first developed antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct methods have been employed to induce parkinsonism using LPS injection: intraperitoneal (i.p), intranasal, and intrastriatal (Bai et al, 2023;Deng et al, 2020;García-Revilla et al, 2022). All these techniques resulted in the degeneration of nigrostriatal dopaminergic neurons, motor dysfunction, and α-synuclein aggregation (Deng et al, 2020;Martins, 2015;Xu et al, 2021). However, from our observations, the intrastriatal injection of LPS exhibited a higher success rate and faster induction of parkinsonism.…”
Section: Discussionmentioning
confidence: 77%